Predictors of purchase intention of luxury south sea pearls and the moderating role of consumer knowledge - T'hart, Brian (2015)
Studies have shown that the Western Australian pearl industry is suffering from a decline. This study aims to gain further insight into this decline by exploring the different antecedents of consumers’ purchase intention of luxury South Sea pearls using the theory of planned behaviour. Further, this study aims to explore the role of consumer knowledge in the purchasing process. This study provides industry practitioners, researchers, policy makers and retailers with new insights into the pearling industry so they are able to better develop products, design branding strategies and form policies which address current consumer behaviour.